2015
DOI: 10.1007/s40262-015-0360-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Pharmacokinetic, Pharmacodynamic and Pharmacogenetic Evaluation of Once-Daily Efavirenz 400 and 600 mg in Treatment-Naïve HIV-Infected Patients at 96 Weeks: Results of the ENCORE1 Study

Abstract: BackgroundENCORE1 demonstrated non-inferiority of daily efavirenz 400 mg (EFV400) versus 600 mg (EFV600) to 96 weeks in treatment-naïve, HIV-infected adults but concerns regarding lower EFV400 concentrations remained. Therefore, relationships between EFV pharmacokinetics (PK) and key genetic polymorphisms with 96-week efficacy and safety were investigated.MethodsRelationships between EFV PK parameters and single nucleotide polymorphisms (SNP; CYP2B6,CYP2A6, CYP3A4, NR1I3, NR1I2, ABCB1) with plasma HIV-RNA (pVL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
1
35
2
Order By: Relevance
“…27,28 However, studies such as ENCORE1, which compared the efficacy of 400 mg of efavirenz to the standard dose of 600 mg at 48 and 96 weeks in treatment-naive patients, suggest that 1,000 ng/mL does not necessarily represent the optimal efficacy concentration cutoff based on the proportion of subjects with both a plasma viral load level ≥200 copies/mL and predicted efavirenz mid-dosing concentrations <1,000 ng/mL compared to >1,000 ng/mL (p = 0.059). 29,30 However, caution is recommended in interpretation based on the limited number of virologic failures and projection of pharmacokinetic parameters to a pharmacodynamic outcome at a much later time point. 30 In addition, a range of possible minimum effective concentrations were suggested (470–760 ng/mL), but additional analysis would be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 However, studies such as ENCORE1, which compared the efficacy of 400 mg of efavirenz to the standard dose of 600 mg at 48 and 96 weeks in treatment-naive patients, suggest that 1,000 ng/mL does not necessarily represent the optimal efficacy concentration cutoff based on the proportion of subjects with both a plasma viral load level ≥200 copies/mL and predicted efavirenz mid-dosing concentrations <1,000 ng/mL compared to >1,000 ng/mL (p = 0.059). 29,30 However, caution is recommended in interpretation based on the limited number of virologic failures and projection of pharmacokinetic parameters to a pharmacodynamic outcome at a much later time point. 30 In addition, a range of possible minimum effective concentrations were suggested (470–760 ng/mL), but additional analysis would be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, caution is recommended in interpretation based on the limited number of virologic failures and projection of pharmacokinetic parameters to a pharmacodynamic outcome at a much later time point. 30 In addition, a range of possible minimum effective concentrations were suggested (470–760 ng/mL), but additional analysis would be required to confirm this. 30 Other studies have reported no correlation between viral suppression and efavirenz exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients having high plasma concentration of EFV should be subjected to closely follow-up. A recent study has shown that once-daily EFV 400 mg dose was so effective than once-daily EFV 600 mg despite lower plasma concentrations obtained, even if this study was probably critical because it compared pharmacokinetic parameters and plasma concentrations obtained at week 4 or 8 and clinical outcome at week 96 [30]. This study included 606 patients with 37% of African and 33% of Asian people.…”
Section: Plasma Concentrations and Adverse Effectsmentioning
confidence: 99%
“…Understanding the clinical relevance of slow EFV metabolism on virologic response is of particular importance for populations in which the minor allele of CYPB2B6 516G>T is common, including patients of African descent. 9-11 Our goal was to determine whether the CYP2B6 516G>T genotype is associated with differential rates of undetectable viral load after having achieved initial HIV suppression. We hypothesized that the 516G>T genotype would be associated with differences in late virologic failure, e.g., either increased rates due to greater CNS toxicity or lower rates due to higher drug concentrations being more permissive of missed doses.…”
Section: Introductionmentioning
confidence: 99%